Sustainability of small-scale fisheries in the middle Negro River (Amazonas - Brazil): A model with operational and biological variables - Inomata, Sandrelly Oliveira; Guadalupe Orellana Gonzalez, Alba Maria [UNESP]; Sanchez Roman, Rodrigo Maximo [UNESP]; Souza, Lucirene Aguiar de; Carvalho Freitas, Carlos Edwar de (Elsevier B.V., 2018)
Fishing is a traditional and important activity in the Amazon Basin, mainly for low-income populations. Nevertheless, Amazonian fish diversity and abundance is threatened by several anthropogenic sources, including deforestation, hydroelectric dams, oil and gas development, global changes and overfishing. This article analyzes the proposal of an alternative model and discusses the predictions obtained from various scenarios and relates them to the management of commercial fishing in the region of the middle Negro River. The model was developed using Stella (R) 9.0, a software package based on system dynamics. Two scenarios were simulated to investigate the dynamics of the fish stock: (a) scenario I: considered a reduction in stock replacement values to half the initial values, a 50% increase in fishing effort, and variable costs and average monthly prices of fish, and; (B) scenario II: analyzed the effect of prohibiting commercial fishing. The planning horizon used was 120 months. Given the results achieved by the simulations, it would be interesting for authorities in the region to have effective control over fishing access and for users to be aware that these natural resources, even though renewable, are susceptible to depletion. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: System dynamics; Fishing; Sustainability; Ecosystem models; Amazonian